Caracterização óptica e térmica de materiais poliméricos via métodos fototérmicos - Rosa, Daniele Toniolo Dias Ferreira (2005)
In the present work photoacoustic spectroscopy is applied on a variety of experimental situations, aiming to determine thermal and spectroscopic, properties of materials. Measurements in different polymers were done: glue, grafted polyethylene and copolymer, europium complex doped blendes, human nail and nafion®. The first study was the analysis of residuals in paper manufacture using the absorption spectra. It demonstrated the similarity between the residue after fabrication and the used glue, not supposed to be present. Secondly, the cross-linking process m grafted vinyltrimetoxysilane on low density polyethylene and the copolymer ethylenelvinyltrimetoxysilane, prepared with factorial design, was monitored through pIIotoacoustic intensity and phase. The optimum point for temperature and concentration of catalyst, using statistical design, indicated the same range for both samples (≈ 5 % and 80 °C). In the study of Eu3+ doped polycarbonate/poly(methylmethacrylate) blends, the spectroscopy and photoluminescence suggested the preferable location of europium complex in polycarbonate phase. The doped blendes presented higher lifetimes and higher quantum efficiency values (≈50%). Normalized thermal diffusivity is higher for blend 20/80 (αmean≈5.6x10-3 cm²/s) whilst the specific heat was almost constant (Cp(mean)≈1.7 Jg-1K-1) for all the used compositions. Yet, the study "in vitro" of human nail thermal diffusivity, using "Open photoacoustic Cell" showed an increase and possible saturation with increasing human age. The average value was found to be (13.7 ±3.6) x 10-4 cm²/s. Finally, the study of thermal diffusivity of nafion® as a function of water content showed that thermal properties can be affected when clusters regions present adsorbed water. For samples "in natura" the average value found for the thermal diffusivity was α=(6.5±0.4)x10-4 cm²/s (Open Photoacoustic Cell) and α=(7.0±0.2)x10-4 cm²/s (Thermal Lens)